Expanding the Clinical Spectrum Associated With GLIS3 Mutations - Dimitri, P. (J Clin Endocrinol Metab, 2015)
CONTEXT: GLIS3 (GLI-similar 3) is a member of the GLI-similar zinc finger protein family encoding for a nuclear protein with 5 C(2)H(2)-type zinc finger domains. The protein is expressed early in embryogenesis and plays a critical role as both a repressor and activator of transcription. Human GLIS3 mutations are extremely rare. OBJECTIVE: The purpose of this article was determine the phenotypic presentation of 12 patients with a variety of GLIS3 mutations. METHODS: GLIS3 gene mutations were sought by PCR amplification and sequence analysis of exons 1 to 11. Clinical information was provided by the referring clinicians and subsequently using a questionnaire circulated to gain further information. RESULTS: We report the first case of a patient with a compound heterozygous mutation in GLIS3 who did not present with congenital hypothyroidism. All patients presented with neonatal diabetes with a range of insulin sensitivities. Thyroid disease varied among patients. Hepatic and renal disease was common with liver dysfunction ranging from hepatitis to cirrhosis; cystic dysplasia was the most common renal manifestation. We describe new presenting features in patients with GLIS3 mutations, including craniosynostosis, hiatus hernia, atrial septal defect, splenic cyst, and choanal atresia and confirm further cases with sensorineural deafness and exocrine pancreatic insufficiency. CONCLUSION: We report new findings within the GLIS3 phenotype, further extending the spectrum of abnormalities associated with GLIS3 mutations and providing novel insights into the role of GLIS3 in human physiological development. All but 2 of the patients within our cohort are still alive, and we describe the first patient to live to adulthood with a GLIS3 mutation, suggesting that even patients with a severe GLIS3 phenotype may have a longer life expectancy than originally described.